The association between physical fitness and mental health among college students: a cross-sectional study - Hong, Yu; Shen, Jiaqi; Hu, Yue; Gu, Yuxuan; Bai, Zhongjiang; Chen, Yu; Huang, Siyi (Frontiers in Public Health, 2024)
Physical inactivity and mental health disorders are emerging threats to public health in China. Previous research on links between exercise and mental wellbeing have focused on clinical populations, with little evidence from the general population, particularly younger adults. We aimed to investigate associations between physical fitness and mental health in Chinese college students.In this series, of cross-sectional observational studies, we enrolled 7468 Chinese college students aged 16-24 years in 199 classes at Changzhou Vocational Institute of Engineering between Sept 1, 2017, and Jun 30, 2018. Exposures of interest were the students' physical fitness level, measured by the Chinese University Students Physique Test. The primary outcomes were mental health situations, measured by the University Personality Inventory (UPI). The multivariable linear regression models were used to assess the relationship between the levels of physical fitness and mental disorders symptoms.Completed mental health and physical fitness data were available for 6724 participants aged 16-24 years. Compared with the failed group, the corresponding levels of difference in overall UPI scores were -1.45 scores (95% CI: -2.45, -0.46; p<0.01) for the passed group and -2.95 scores (95% CI: -4.13, -1.77; p<0.01) for the good group. Similar results were observed in the four different aspects of psychotic disorder symptoms.There was a significantly negative correlation between the level of physical fitness and phycological situations among Chinese college students. Our findings highlight the psychological situations of students with low physical fitness levels should be concerned.